1985
DOI: 10.1007/bf02554142
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection of pulmonary metastases from colorectal adenocarcinoma

Abstract: From 1962 to 1982, 27 patients with pulmonary metastases as the only site of recurrent colorectal carcinoma underwent pulmonary resection at Roswell Park Memorial Institute. Only five of these patients had symptomatic pulmonary lesions. No postoperative mortality occurred. The median survival after pulmonary resection was 27 months. Five patients are alive presently without recurrent colorectal cancer and two patients are alive with recurrent pulmonary metastases. Patients with solitary lesions had a better su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…Some studies indicated the number of pulmonary metastases as a prognostic factor. 3,5,7,9,[13][14][15][16][17] Other studies reported the maximum size of lung metastasis, 5,12 disease-free interval, 10,18 prethoracotomy carcinoembryonic antigen (CEA) level, 7,16 hilar/mediastinal lymph node metastasis, 12,13 and the history of other metastatic sites 13 as significant prognostic factors. However, no definitive indications have been established at present.…”
mentioning
confidence: 99%
“…Some studies indicated the number of pulmonary metastases as a prognostic factor. 3,5,7,9,[13][14][15][16][17] Other studies reported the maximum size of lung metastasis, 5,12 disease-free interval, 10,18 prethoracotomy carcinoembryonic antigen (CEA) level, 7,16 hilar/mediastinal lymph node metastasis, 12,13 and the history of other metastatic sites 13 as significant prognostic factors. However, no definitive indications have been established at present.…”
mentioning
confidence: 99%
“…The liver is often the first site of metastasis from colorectal cancer and may be the only site of spread in as many as 30–40% of patients with advanced disease 5 . Lung metastasis is the most common extra‐abdominal site of metastasis and is the second most common site of metastasis 6,7 . Surgery remains the only potential curative treatment for patients with colorectal metastasis, especially for lung metastasis.…”
Section: Discussionmentioning
confidence: 67%
“…7 Where technically feasible, resection of metastatic deposits in the lungs or liver is advisable. 25,26 The chemotherapeutic agents in use include 5-FU, irinotecan, leucovorin, and the more recent anti-vascular endothelial growth factor, bevacizumab. 7 Radiotherapy finds use in cases of rectal cancer to reduce the risk of local recurrence.…”
Section: Discussionmentioning
confidence: 99%